Stator Electrically-excited Brushless Synchronous Machine and Its Inductance Calculation - JIA Guanglong; CHEN Zhichu; HU Yongfeng; LI Weiye (Kongzhi Yu Xinxi Jishu)
It is known that the reliability of electrically excited synchronous machine with brush is reduced. It proposed a new type of electrically excited synchronous machine, the stator electrically-excited brushless synchronous machine (SEBSM). In this paper, the structure characteristic and working principles of the SEBSM were introduced, the air-gap magnetic field of the machine was analyzed, and its magnetic field modulation principle and mechanism of electromechanical energy conversion were further revealed. Based on winding function and superposition method, inductance parameter calculation model of the SEBSM was set up, the inductance parameters of the SEBSM prototype with 8+4 poles were calculated, and the error between the calculated and tested inductances is within ±2.5%, which justified the correctness of the inductance calculation model.